The influencing factors of hoteliers in malaysia to affiliate with certain Online Travel Agencies (OTAs) / Ramli Saad ... [et al.] - Saad, Ramli; Wan Mahamad, Wan Shahrul Aziah; Mohd Ghazalic, Nurul Azizah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
The number of Online Travel Agencies (OTAs) has increased dramatically over the last couple of years. This shows that the existing of intermediaries particularly in hospitality industry has transformed transforming from physical to virtual concept. It is a convenient way of making a booking, either on the computer or via a mobile device and could be made anywhere at any given time. Thus, this paper aims to empirically examine the influencing factors of hoteliers in Malaysia to affiliate with certain Online Travel Agencies (OTAs). A sample of two hundred hoteliers was randomly chosen in this survey with one hundred and fifty five feedbacks received. Regression analysis has been used to determine the influencing factors (commission requested, service provided, number of competitors and customer base) of hoteliers in Malaysia to affiliate with certain Online Travel Agencies (OTAs). The result from hypotheses testing has shown that service provided and customer base have significant influence. Results which were obtained from the study can be useful in the future for Online Travel Agencies (OTAs) to make better decision in dealing with their hoteliers particularly during the current Industrial Revolution 4.0 era.